2013
DOI: 10.1371/journal.pone.0084206
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Stromal Cells Contain Phenotypically Distinct Adipogenic Progenitors Derived from Neural Crest

Abstract: Recent studies have shown that adipose-derived stromal/stem cells (ASCs) contain phenotypically and functionally heterogeneous subpopulations of cells, but their developmental origin and their relative differentiation potential remain elusive. In the present study, we aimed at investigating how and to what extent the neural crest contributes to ASCs using Cre-loxP-mediated fate mapping. ASCs harvested from subcutaneous fat depots of either adult P0-Cre/or Wnt1-Cre/Floxed-reporter mice contained a few neural cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 47 publications
0
43
0
Order By: Relevance
“…neuronal cells) have been induced from MSCs , mostly by cytokine stimulation and/ or gene introduction [Makino et al, 1999;Pittenger et al, 1999;Spees et al, 2003;Dezawa et al, 2004;Dezawa et al, 2005;Oyagi et al, 2006]. Furthermore, several studies have indicated that some adult bone marrowderived MSCs (BMSCs) and adipose-derived stem cells (ADSCs) are derived from the neural crest, an ectodermal lineage, which might provide an explanation for the ability of MSCs to generate Schwann cells [Billon et al, 2007;Takashima et al, 2007;Nagoshi et al, 2008;Sowa et al, 2013]. These findings indicate that Schwann cells, which belong to the ectodermal lineage, could also be induced from MSCs.…”
Section: Schwann Cells Generated From Mscs Function Like Authentic Scmentioning
confidence: 99%
“…neuronal cells) have been induced from MSCs , mostly by cytokine stimulation and/ or gene introduction [Makino et al, 1999;Pittenger et al, 1999;Spees et al, 2003;Dezawa et al, 2004;Dezawa et al, 2005;Oyagi et al, 2006]. Furthermore, several studies have indicated that some adult bone marrowderived MSCs (BMSCs) and adipose-derived stem cells (ADSCs) are derived from the neural crest, an ectodermal lineage, which might provide an explanation for the ability of MSCs to generate Schwann cells [Billon et al, 2007;Takashima et al, 2007;Nagoshi et al, 2008;Sowa et al, 2013]. These findings indicate that Schwann cells, which belong to the ectodermal lineage, could also be induced from MSCs.…”
Section: Schwann Cells Generated From Mscs Function Like Authentic Scmentioning
confidence: 99%
“…Neural crest-derived adipose stem cells (NCDASC) are technically a subpopulation within ASC, showing similar MSC markers as their non-neural crest derived counterparts, but demonstrate a multipolar morphology for neural crest progenitors (i.e. Nestin and Sox2) as well as preadipocytes (CD24, CD34, S100) [75,76] . However, while NCDASC maintain their predilection towards an adipogenic lineage, they show reduced osteogenic and chondrogenic potential [75] .…”
Section: Profile and Identitymentioning
confidence: 99%
“…Nestin and Sox2) as well as preadipocytes (CD24, CD34, S100) [75,76] . However, while NCDASC maintain their predilection towards an adipogenic lineage, they show reduced osteogenic and chondrogenic potential [75] . Another group also confirmed that a subset of adipocytes originate from the neural crest; as well, the neural-crest derived subpopulation under the proper stimulation will differentiate into adipocytes [77] .…”
Section: Profile and Identitymentioning
confidence: 99%
“…Similar to the differences seen in the osteogenic potential of neural crest vs. mesoderm-derived calvarial bones, the developmental origin of ASCs may contribute to their adipogenic ability. Sowa et al found that, albeit small, the subpopulation of ASCs derived from the neural crest is phenotypically unique from non-neural crest derived ASCs, and restricted primarily to adipogenic differentiation [61]. [64].…”
Section: Cd31mentioning
confidence: 99%